2012
DOI: 10.1097/scs.0b013e31824dba1f
|View full text |Cite
|
Sign up to set email alerts
|

Complex and Compound Odontomas

Abstract: Odontomas are hamartomas not rarely encountered by oral and maxillofacial surgeons. Odontomas usually determine delayed eruption; thus, in case of any dentition anomaly or jaw deformation in children and adolescents, it is very important to investigate the presence of possible odontomas with radiographs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 18 publications
3
48
0
14
Order By: Relevance
“…Not rare, the patient search for dental assistance due to the lack of eruption of a permanent tooth. Because the majority of odontomas are asymptomatic, and seldom causes swelling, pain, suppuration and/or bone expansion, this kind of tumour use to be discovered accidentally, after routine radiograph examination 7 13 15. In general, odontomas causes the impaction of permanent teeth as presented in this case, but sometimes they can be associated with primary dentition 10–13…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Not rare, the patient search for dental assistance due to the lack of eruption of a permanent tooth. Because the majority of odontomas are asymptomatic, and seldom causes swelling, pain, suppuration and/or bone expansion, this kind of tumour use to be discovered accidentally, after routine radiograph examination 7 13 15. In general, odontomas causes the impaction of permanent teeth as presented in this case, but sometimes they can be associated with primary dentition 10–13…”
Section: Discussionmentioning
confidence: 90%
“…It has been suggested that the odontoma, once enucleated, usually does not recur in young children, but a close follow-up is needed 11. If odontomas are extirpated early without disturbing the underlying tooth germ, the eruption of the impacted tooth can be expected spontaneously 7 16. In a retrospective investigation of 73 cases of odontomas, 53.2% of the impacted teeth erupted after the surgical removal of the odontogenic tumours 15.…”
Section: Discussionmentioning
confidence: 99%
“…Si no aparecen signos ni síntomas, esta lesión puede permanecer en el hueso muchos años sin producir manifestaciones clínicas, tales como formación de quistes dentígenos o quiste odontogénico epitelial calcificante (Fernandes et al, 2005). El tratamiento de elección para estos casos es la enucleación simple de la lesión, siendo un tratamiento conservador (Boffano et al, 2012).…”
Section: Discussionunclassified
“…Complex odontomas are more prevalent than compound odontomas 12. The aetiology of odontomas is due to gene mutations or interference, or possibly postnatal genetic control of odontogenesis.…”
Section: Discussionmentioning
confidence: 99%